Myocardial infarction in pregnant women - Janion, Marianna; Janion-Sadowska, Agnieszka (Przewodnik Lekarza/Guide for GPs, 2010)
Myocardial infarction in pregnant women is an extremely rare event. However, it also is a dangerous disease, associated with unfavorable prognosis both for mother and child, which requires intensive care from a multidisciplinary team of physicians and nurses. There are justified concerns that, due to the current trend by women to delay childbearing even until the fourth or fifth decades of their lives as well as due to the development of assisted reproduction techniques, which allow women who have diabetes, hypertension and obesity to get pregnant, the frequency of pregnancy-related myocardial infarctions may increase in the upcoming years. It is necessary to identify high risk women in order to apply early prevention and to diagnose any potential complications. Treatment does not differ substantially from standard therapy for myocardial infarction. Early diagnosis and application of appropriate treatment significantly improves clinical outcome both for mother and the child.